A devastating duo: widespread toxoplasmosis in an immunocompromised host - Cheong, Xiong Khee; Zainulabid, Ummu Afeera; Kori, Najma; Periyasamy, Petrick (Elsevier Ltd, 2025)
Toxoplasma gondii is an intracellular protozoan that commonly causes reactivation of latent infection, manifesting as cerebral toxoplasmosis in immunocompromised hosts, particularly people living with HIV. Ocular toxoplasmosis can manifest as severe bilateral retinochoroiditis in these individuals. We describe a case of concurrent cerebral and ocular toxoplasmosis in a newly diagnosed HIV-infected individual who recovered with antiparasitic therapy.